2020
DOI: 10.1016/j.adolescence.2020.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐cognitive variables involved in the relationship between violence exposure at home and child‐to‐parent violence

Abstract: Introduction:The aim of the current cross-sectional study was to examine the role of socialcognitive processing in the relation between violence exposure at home and child-to-parent violence. Methods: The study included 1,624 adolescents (54.9% girls) aged between 12 and 18 years (M age = 14.7,S D= 1.7 years) from Jaén and Oviedo (Spain) who completed a set of questionnaires about violence exposure, child-to-parent violence and social-cognitive processing. Results: The data revealed that exposure to violence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 50 publications
11
49
0
4
Order By: Relevance
“…In addition, the literature on general violent behavior has indicated that this variable is specifically linked to reactive violence (Poulin and Boivin, 2000). Our study provides additional evidence on this topic, since anger was positively correlated with CPV toward the father and toward the mother motivated by reactive reasons, which is consistent with the study by Contreras et al (2020). Therefore, although some studies have previously analyzed hostile attribution and anger in the context of CPV, our data further delve into the relationship between these variables and this type of family violence, showing its specific relationship with reactive CPV toward both fathers and mothers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, the literature on general violent behavior has indicated that this variable is specifically linked to reactive violence (Poulin and Boivin, 2000). Our study provides additional evidence on this topic, since anger was positively correlated with CPV toward the father and toward the mother motivated by reactive reasons, which is consistent with the study by Contreras et al (2020). Therefore, although some studies have previously analyzed hostile attribution and anger in the context of CPV, our data further delve into the relationship between these variables and this type of family violence, showing its specific relationship with reactive CPV toward both fathers and mothers.…”
Section: Discussionsupporting
confidence: 90%
“…These results are confirmed in samples of young people aged 18-25 years, with anger being a predictor of CPV toward both parents (Simmons et al, 2020). Other studies have delved further into this variable, indicating that anger predicts reactive CPV toward both the father and the mother (Contreras et al, 2020).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Girls were also more victims of IPV, though it is important to keep in mind that the search for information may already have been skewed by the sex of the person assessed as far as it is a variable designed, initially, for girls. Violence exposure at home affects social cognitive pro-cessing and should be included in CPV prevention and treatment plans (Contreras, León, & Cano-Lozano, 2020).…”
Section: Characteristics Of Offenders and Victimsmentioning
confidence: 99%